A EPISTEMOLOGY METHODOLOGY OF IMRE LAKATOS'S SCIENTIFIC RESEARCH PROGRAM AND CONTRIBUTION TO ISLAMIC SCIENCE - Muhamad Fadli (Sekolah Tinggi Agama Islam Sadra, 2023)
This study aims to look at the contribution of Imre Lakatos’ scientific research program to Islamic scholarship. This study focuses on the relevance between the scientific research program and the integration-interconnection paradigm initiated by Amin Abdullah. This research uses a qualitative approach with a library research method, tracing writings that have a connection with the theme raised in the books and relevant recent articles. The study results found that Imre Lakatos’ scientific research program is the result of the development of its predecessors, Popper’s falsification and Thomas Kuhn’s scientific revolution. Scientific research has three important elements: 1) hard-core, which is the core of research that cannot be disturbed; 2) protective belt, which protects the hard core from being eliminated: and 3) a series of theories, which contains interrelated theories and will give birth to new theories. In Islamic scholarship, the same thing happens, except that in Islamic scholarship, no matter how complex the problem is, the hardcore can never be replaced, unlike the Lakatos research program that adapts to the context of the problem. One of the fruits of the Lakatos concept is the presence of the Integration-Interconnection paradigm initiated by Amin Abdullah at UIN Sunan Kalijaga to connect religious science with other sciences through research. Three criteria must be met so that the concept of integration-interconnection can be used in the scientific research paradigm: recognized by most of the scientific community, has become a characteristic in society, and has produced many works from the concept of integration-interconnection.